2021
DOI: 10.3389/fpsyt.2021.728535
|View full text |Cite
|
Sign up to set email alerts
|

Breaking It Down: Investigation of Binge Eating Components in Animal Models to Enhance Translation

Abstract: Binge eating (BE) is a core eating disorder behavior that is present across nearly all eating disorder diagnoses (e. g., bulimia nervosa, binge eating disorder, anorexia nervosa binge/purge subtype), and is also widely present in the general population. Despite the prevalence of BE, limited treatment options exist and there are often high rates of relapse after treatment. There is evidence showing that genetic factors contribute to the heritability of BE and support for biological contributions to BE. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 145 publications
(297 reference statements)
0
14
0
2
Order By: Relevance
“…However, sometimes regular food pellets or chow can serve as the reward, which would not be traditionally termed palatable food; yet several studies have shown that rodents can have preferences for and/or binge-like episodes with these foods. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sometimes regular food pellets or chow can serve as the reward, which would not be traditionally termed palatable food; yet several studies have shown that rodents can have preferences for and/or binge-like episodes with these foods. 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…However, sometimes regular food pellets or chow can serve as the reward, which would not be traditionally termed palatable food; yet several studies have shown that rodents can have preferences for and/or binge-like episodes with these foods. 37,38 Despite a vast body of literature on the neurobiological basis of BED, differentiation between BED and FA has rarely been made in previous studies. Most studies compare cravings and withdrawal symptoms owing to hyperpalatable foods with an opioid-related addiction.…”
Section: Binge-eating Disorder (Bed)mentioning
confidence: 99%
“…The BE paradigm used across all experiments is based on previous work using intermittent PF access schedules in rodents (see review in Hildebrandt & Ahmari, 2021). Intermittent PF access schedules mimic multiple features of BE in humans– e.g., BE is episodic and occurs over a short (~two hour) period of time (American Psychiatric Association, 2013), and individuals consume food that is typically low in nutrition but high in palatability (Boggiano et al, 2007; Furlong et al, 2014; Hildebrandt et al, 2014; Hildebrandt et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The BE paradigm used across all experiments is based on previous work using intermittent PF access schedules in rodents (see review in Hildebrandt & Ahmari, 2021).…”
Section: Experiments 1: Examination Of Early Trajectories Of Binge-li...mentioning
confidence: 99%
See 1 more Smart Citation